Ethical Political Education in the Digital Era: Challenges and Opportunities in Indonesia - Sandi S, Renda; Vera (Communication in Research and Publications (CRP), 2025)
The development of digital technology has changed the political landscape of Indonesia, creating opportunities and challenges in ethical political education. This study analyzes the implementation of ethical political education in Indonesia's digital era with a focus on its challenges and opportunities. Based on a literature study with a qualitative approach, this study explores the phenomenon of filter bubbles, digital literacy, and the integration of Pancasila values ​​in forming ethical digital citizens. Data from the Ministry of Communication and Information shows that more than 100 thousand negative content was spread on social media in 2023, while Indonesia's digital literacy index in 2022 was still at a moderate level (3.54). The findings show that political education faces significant challenges due to the filter bubble and echo chamber phenomena that strengthen polarization and hinder constructive dialogue. The Contextual Teaching and Learning (CTL) approach in civic education has proven effective in increasing students' political awareness, but the implementation of Pancasila values ​​in the curriculum is still uneven. Ethical political education requires a collaborative strategy between educational institutions, government, and civil society to design policies and programs that are responsive to digital dynamics. Recommendations include the integration of digital literacy and political ethics in the formal curriculum, the development of teacher training programs, increasing public awareness of the dangers of filter bubbles, and a holistic approach in teaching Pancasila values. With the implementation of this strategy, ethical political education is expected to form citizens who are critical, responsible, and have integrity in facing the complexities of digital democracy.